Seismic strengthening of heritage masonry buildings using fiber-reinforced paint: Numerical validation and shake table testing for enhanced energy dissipation and safety - Htet, Phyo Min; Ejaz, Ali; Gadagamma, Chaitanya Krishna; Hussain, Qudeer; Saingam, Panumas; Khaliq, Wasim; Sua-iam, Gritsada; Chatveera, Burachat; Suparp, Suniti (My University, 2025)
This research aimed to strengthen heritage masonry buildings using fiber-reinforced paint (FRP) and evaluate seismic responses, including the Arias intensity scale, peak acceleration, peak displacement, lateral drift, and dissipated energy. In the numerical phase, the prototype model was studied using the Applied Element Method (AEM) and similitude law, resulting in a well-performing scaled model with error percentages of approximately 5 % for element results and 4 % for spring results. This validated the model's accuracy, leading to its adoption for experimental work. The experimental phase involved shake table testing of the scaled models, revealing that the unreinforced model (URM) collapsed at run 44, whereas the FRP-retrofitted specimen collapsed at run 52. Cracks in the FRP-retrofitted specimen began at run 39, compared to run 10 in the URM, with the FRP-retrofitted specimen arch masonry roof remaining undamaged prior to collapse. The FRP-retrofitted specimen demonstrated superior seismic performance, with an Arias intensity scale 3.67 times higher, base shear over 400 % greater, and lateral drift 10.89 times higher than the URM, indicating its ability to resist significant displacement and deform plastically. Additionally, the FRP-retrofitted specimen exhibited stable, wider hysteretic loops, leading to 6.1 times more energy dissipation than the URM, thereby offering enhanced safety for occupants.
Keywords: Applied element method; Fiber-reinforced paint; Masonry; Shake table